Optimization of Alpha-Amylase Production by Bacillus amyloliquefaciens Grown on Orange Peels - Uygut, M. Ali; Tanyildizi, M. Saban (Springer International Publishing Ag, 2018)
The aim of this study was to optimize the production of alpha-amylase using orange peels (OP) and cheese whey under semi-solid-state fermentation conditions with Bacillus amyloliquefaciens. The experimental studies were executed according to statistical design methodology. Firstly, concentrations of solid substrate and medium components and inoculum volume were investigated by Placket-Burman design, and the important variables for enzyme production were determined amount of OP, glucose, cheese whey and yeast extract. Second, the four components were examined for optimization of alphaamylase using central composite design. The result of ANOVA test shows that the linear effect of OP, glucose and yeast extract concentration and the quadratic effect of OP and yeast extract concentration were significant on alpha-amylase activity. The analysis results also indicated that interactions between OP and yeast extract, glucose and cheese whey affected the enzyme production significantly. The maximum enzyme activity (220 U/ml) was obtained at the concentration of OP (89 g/l), yeast extract (2.50 g/l), glucose (10.50 g/l) and whey (40 ml/l).
Keywords: Alpha-amylase; B. amyloliquefaciens; Orange peels; Response surface methodology